Occupational Accidents on Transport Workers - Yulia Roma Ito; Gerry Silaban; Eka Lestari Mahyuni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Health and safety at work are aspects related to the welfare of someone who carries out activities within the household, service agency or project implementer. Work safety that is important to note is that work safety can also be expressed as an effort to protect workers against hazards and risks that can occur due to processes and interactions that occur in the workplace. The study was to analyze factors that affect work accidents in transportation workers The study was a qualitative with cross-sectional approach. Eighty-nine respondents were involved in this study, selected using a simple random sampling technique. Data were collected using questionnires and analyzed using chi-square and multiple logistics regression. The results show that there was a relationship between the transport load, physical condition, work and attitude with work accidents with work accidents for transportation workers. The transport load variable is the most dominant variable related to the occurrence of accidents in transportation workers. It is expected that the leaders of trade unions throughout Indonesia will provide a good work attitude by sticking posters about good lifting and transporting work attitudes. Abstrak: Kesehatan dan keselamatan kerja merupakan aspek yang berkaitan dengan kesejahteraan seseorang yang melakukan kegiatan di dalam rumah tangga, instansi pelayanan atau pelaksana proyek. Keselamatan kerja yang penting untuk diperhatikan adalah keselamatan kerja juga dapat dinyatakan sebagai upaya untuk melindungi pekerja dari bahaya dan risiko yang dapat terjadi akibat proses dan interaksi yang terjadi di tempat kerja. Penelitian ini untuk menganalisis faktor-faktor yang mempengaruhi kecelakaan kerja pada pekerja transportasi. Jenis penelitian ini adalah kualitatif dengan pendekatan cross sectional. Delapan puluh sembilan responden terlibat dalam penelitian ini, dipilih dengan menggunakan teknik simple random sampling. Data dikumpulkan dengan menggunakan kuesioner dan dianalisis menggunakan chi-square dan regresi logistik berganda. Hasil penelitian menunjukkan bahwa ada hubungan antara beban angkutan, kondisi fisik, dan sikap kerja dengan kecelakaan kerja dengan kecelakaan kerja pada pekerja angkutan. Variabel beban angkutan merupakan variabel yang paling dominan berhubungan dengan terjadinya kecelakaan pada pekerja angkutan. Diharapkan para pimpinan serikat pekerja di seluruh Indonesia memberikan sikap kerja yang baik dengan menempelkan poster tentang sikap kerja angkat dan angkut yang baik.